Utilization of Literacy Tree Media in Improving The Reading Ability of Low-Grade Students at SD Inpres Dhereisa - Gulo, Oktaviani; Ita, Efrida; Meka, Marsianus; Ngura, Elisabeth Tantiana (JURNAL DIMENSI PENDIDIKAN DAN PEMBELAJARAN, 2025)
This research was carried out on the problem of low reading ability of students and the lack of use of learning media that makes students easily bored. The purpose of this study is to determine the use of literacy tree media in improving the reading ability of grade III students at Inpres Dhereisa Elementary School. The type of research used is qualitative research using observation, interviews, and documentation. The data analysis techniques used are data collection, data reduction, data presentation, and conclusion drawing/verification stage. The results of the study showed that through the application of the Literacy tree, 83.33% of students were fluent in reading and 16.66% of students had difficulty reading. The literacy tree plays a positive role in stimulating students' interest in reading and can increase students' reading ability. However, there were also several obstacles such as limited book collections and lack of active participation from all school residents. The use of literacy trees is successful but not optimal, so it is recommended for the development of the use of literacy trees to be more effective in supporting the improvement of students' reading skills.